(untitled) (Journal of Atomic and Molecular Sciences, 2019)
A novel biochemical sensor based on molecular imprinted technology was built through electropolymerization. One of the keystones of the technology is the discovery and application of new conductive polymer. Herein, a new conductive ferrocenyl chalcone derivative: [1-Oxo-3-(3-thienyl)-2-propen-1-yl] ferrocene (OTPylFc) was synthesized and characterized by nuclear magnetic resonance (NMR) and finally adopted in the technology. The OTPylFc and pyrrole mixture was eletropolymerized in this work and showed satisfying result in improving current peaks. The linear relationship was 1.729× 10^-6 M to 6.916 × 10^-4 M. It is believed that the structure and their conductive analogs formed co-polymers would have a promising prospect in future research.